Vertical content feeds and cognitive adaptation - Yaroshenko, Denys (Запоріжжя: ТДАТУ, 2026)
People consume information very fast due to algorithms. Many years ago, people used internet to find something specific, but today, the internet finds us. When we walk on the street, sit in a bus, or even listen to a lecture, we always look in our phones. Platforms like YouTube Shorts, TikTok, Instagram Reels are very popular because they use very short videos to catch our attention. This massive flow of fast information is changing how our brain works. It is very important to study this problem today, because modern folks spend many hours using their phones every day, and it’s changing their life.
Keywords: cognitive adaptation; content feeds